Flexible Multifunctionalized Carbon Nanotubes‐Based Hybrid Nanowires. (26th May 2015) - Wang, Nan; Jiang, Di; Ye, Lilei; Murugesan, Murali; Edwards, Michael; Fu, Yifeng; Liu, Johan
<x xml:space="preserve">Abstract</x> In this work, flexible multifunctionalized carbon nanotube (CNT)‐based hybrid nanowires are synthesized through surface modification processes. The good dispersability of the hybrid nanowire in polar solvents facilitates directly making fine patterns with a minimum width of 40 μm for applications of flexible and stretchable circuits (FSCs). The hybrid nanowire possesses a flexible and highly conductive structure which demonstrates stable electro‐mechanical properties on polydimethylsiloxane (PDMS) substrates under large structural deformation. FSCs fabricated from the hybrid nanowires show a constant resistance of 0.096 Ω □−1 (equivalent of a resistivity 0.96 Ω μm) under repeated bending cycles. The FSCs also have a low and stable sheet resistance of 0.4 Ω □−1 for strains up to 30%, which is almost four orders of magnitude lower than that of pure CNT samples (1316 Ω □−1). Further improved stretchability and electro‐mechanical properties (0.1 Ω □−1, at the strain of 100%) are achieved with a prestrain PDMS substrate. Repeated deformation tests demonstrate the high reliability of FSCs. The observed stable and reliable electro‐mechanical performance of FSCs suggests the potential use of the material in wearable and portable electronics.